Power‐controlled flash spark plasma sintering of gadolinia‐doped ceria. Issue 2 (22nd October 2020) - Tyrpekl, Vaclav; Cologna, Marco; Holzhäuser, Michael; Svora, Petr
Abstract: Electric field‐assisted sintering (FAST) is a rapidly growing scientific and engineering domain. In the present paper, we describe the process of flash sintering (FS) in a configuration of classical spark plasma sintering (SPS) (graphite punch and boron nitride (BN) die), also called flash spark plasma sintering (FSPS). The densification process of Gd0.1 Ce0.9 O2‐x powder is studied in detail with a focus on the transition from FAST to FS. We discuss the electrical, geometrical, and thermal evolution of the process and the characteristics of the final compacts. Low electrical fields are sufficient for the onset of FS. Ceria is a material difficult to sinter by FAST techniques due to its known mechanochemical transformations. We observed the disintegration of pellets after experiments with well‐pronounced flash event.